Study on Carrying Capacity of Square shell and Parameter analysis - Wang , Peng; Cao, Heyun; Niu, Qingyong; Zhang , Hao (Transactions on Environment, Energy and Earth Sciences, 2024)
Square shell is one structural type which is quite common to be seen in engineering. This paper focuses on the carrying capacity of square shell, and studies the influence of round radius and shell thickness on the ratio of mass to external volume and load factor under linear buckleing of shell. Numerical results show that, With the increase of round radius, the ratio will first decrease, then increase and approach that of circular shell, while the load factor will also increase. With the increase of shell thickness, the ration of shell will increase and the load factor will rapidly increase. This will help to better design of pressure hull of submarines.